P0230IMMUNOSUPPRESSIVE TREATMENT DOES NOT IMPROVE KIDNEY SURVIVAL IN PATIENTS WITH HCV CRYOGLOBULINAEMIA TREATED WITH DIRECT-ACTING ANTIVIRALS. (6th June 2020) - Ana, Pérez de José; Carbayo, Javier; Pocurull, Anna; Huerta, Ana; Cases Corona, Clara Maria; Bada Bosch, Teresa; Shabaka, Amir; Ramos Terrada, Natalia; Martinez Valenzuela, Laura; Goicoechea, Marian
Abstract: Background and Aims: Since the introduction of direct-acting antivirals (DAAs), few data have been published about kidney outcome in hepatitis C virus related mixed cryoglobulinaemia (HCV-MC) patients treated with combined DAAs and rituximab. We aimed to asses if combined treatment with DAAs and rituximab in patients with HCV-MC improves kidney survival and immunological response. Method: Observational, multicentre, cohort study of 100 patients with HCV-MC from 14 Spanish centres treated with DAAs. Patients were followed up for a median duration of 138 months (11.5 years). Long-term kidney survival and immunological response were evaluated based on immunosuppressive treatment received. Kidney event was defined as duplication of creatinine level or 50% decrease in glomerular filtration rate, dependence on renal replacement therapy or non-reduction of proteinuria by 50% compared to baseline. Immunological response was defined as the decrease in cryocrit ≤1%. Results: Sustained virological response was attained in 98 (98%) patients. 49 patients were treated with immunosuppressive treatment associated with DAAs, 26 with rituximab and the rest (23) with steroids and/or cyclophosphamide. Patients receiving immunosuppressive treatment had higher basal cryocrit (6.3±4.5 vs 3.8±3.9%, p=0.011), lower glomerular filtration rate (55±27 vs 68±25 ml/min/1.73 m 2 ) and more haematuria (p=0.001). The 26 patients treated with rituximab had more severe disease: higher viral load (p=0.001), cryocrit (p=0.011), proteinuria (p=0.004), microhaematuria (p=0.012) and hypertension (p=0.012) and lower glomerular filtration rate (p=0.001). 15 patients had a kidney event at the end of follow-up. Predictive variables of kidney events were lower age (HR 0.94, 95%CI 0.89-0.99; P= 0.038) and lower glomerular filtrate rate (HR 0.97, 95%CI 0.94-0.99; p=0.026), in a model adjusted to proteinuria and microhaematuria. Immunosuppressive treatment with or without rituximab did not change kidney survival. Regarding the immunological response, only 19 patients had a cryocrit >1% at the end of follow-up. There were no differences in age, viral load, proteinuria and basal glomerular filtration rate between these patients with no immunological response and those who had a sustained immunological response over time. The only differences between these two groups were a higher basal cryocrit and a minor C4 levels. Immunosuppressive treatment with or without rituximab did not changed the immunological response. Conclusion: Patients with more severe HCV-MC are those receiving immunosuppressive treatment. However, immunosuppressive treatment does not change kidney survival nor immunological response of these patients in the long term.